Birth of the Renaissance - Hribar, Maxino Nicora; RCS Editori Rizzoli Corriere (New York RCS Sansoni Editore Spa-Firenze)
Presents key masterpieces of artistits during the birth of the Renaissance like Alberti, Brunelleechi Luca della Robbia, Donatello, Michelozzo, martini, Giotto, Masaccio.
Based on the book Storia de'll Arte Italliana Guillo Carlo Argan
Keywords: Art, Renaissance; Paiting Renaissance; Art -- Italy